Immunotherapy in Combination with Chemotherapy for Triple-Negative Breast Cancer - Meléndez-Solano, Elizabeth; Chapa, Christian; Stevens Barrón, Jazmín Cristina (2023)
Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer that lacks estrogen and progesterone receptors and does not overexpress the human epidermal growth factor receptor 2 (HER2). Previous treatment options for TNBC were limited to chemotherapy alone, resulting in a poor patient prognosis. In 2018, an estimated 2.1 million new cases of breast cancer were diagnosed globally, with the incidence increasing by 0.5% annually from 2014 to 2018. The exact prevalence of TNBC is difficult to determine because it is based on the absence of certain receptors and overexpression of HER2. Treatment options for TNBC include surgery, chemotherapy, radiation therapy, and targeted therapy. The available evidence suggests that combination immunotherapy using PD-1/PD-L1 inhibitors may be a promising treatment option for metastatic TNBC. In this review, we evaluated the efficacy and safety of different immunotherapies regimens for the treatment of TNBC. In many clinical trials, the overall response rate and survival were better in patients treated with these drug combinations than those treated with chemotherapy alone. Although definitive treatments are not within reach, efforts to gain a deeper understanding of combination immunotherapy have the potential to overcome the urge for safe and effective treatments.